2006
DOI: 10.2116/analsci.22.1175
|View full text |Cite
|
Sign up to set email alerts
|

Onboard Determination of Submicromolar Nitrate in Seawater by Anion-Exchange Chromatography with Lithium Chloride Eluent

Abstract: Nitrogen is an essential element for phytoplankton growth in aquatic environments. Nitrate is the main nutrient supporting this production in the open ocean, and the supply of nitrate often controls primary production in oligotrophic areas. Excluding the high-latitude and eastern equatorial regions of the Pacific, the surface waters of the North and South Pacific Ocean from about 40˚ N to 40˚ S are relatively depleted in nitrate. In the North Pacific subtropical gyre, nitrate concentrations are typically below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Porewater was obtained from 10-to 20-cmlong WRCs; the total alkalinity and the ammonium, sulfate, and methane concentrations were determined previously (26). The nitrate concentration was measured by ion chromatography using a high-capacity anion exchanger (TSK-gel SAX column; Tosoh) with UV detection (LC-10Ai and SPD-10A; Shimadzu) (29,30). The lower detection limit of the nitrate concentration was 0.3 M, and the reproducibility was better than 10%.…”
Section: Methodsmentioning
confidence: 99%
“…Porewater was obtained from 10-to 20-cmlong WRCs; the total alkalinity and the ammonium, sulfate, and methane concentrations were determined previously (26). The nitrate concentration was measured by ion chromatography using a high-capacity anion exchanger (TSK-gel SAX column; Tosoh) with UV detection (LC-10Ai and SPD-10A; Shimadzu) (29,30). The lower detection limit of the nitrate concentration was 0.3 M, and the reproducibility was better than 10%.…”
Section: Methodsmentioning
confidence: 99%
“…The analytical precision was generally estimated to be within 3 % for the seawater analysis. The nitrate concentration was determined onboard using a liquid chromatograph (Shimadzu, LC10AI) with a UV detector (λ ¼ 220 nm, Shimadzu, SPD10AVP) following a modified protocol (Maruo et al 2006). To eliminate interference from major anions such as Cl À and SO 4 2À , a highcapacity anion exchange column (Tosoh, TSK gel-SAX, 4.6 Â 50 mm) was used with a 1 M sodium chloride eluent at a flow rate of 0.8 ml/min.…”
Section: Chemical Characteristics Of Hydrothermal Fluidsmentioning
confidence: 99%
“…8 By using alkaline and alkaline earth metal chlorides, the selectivity for each analyte was enhanced by decreasing the concentration of the eluent anion, but the order of elution could not be changed.…”
Section: Effect Of Cadmium Ion In Potassium Chloride Eluent On the Rementioning
confidence: 99%
“…[5][6][7] Our laboratory has reported that the separation factor between bromide and nitrate can be modified through the use of alkaline metal cations along with a high-concentration eluent and high-capacity anion-exchange resin. 8 This method was used to determine nitrate in seawater. When using alkaline and alkaline earth metal cations in the previous study, the separation factor of nitrate relative to bromide was found to depend on both the countercation used and its concentration.…”
Section: Introductionmentioning
confidence: 99%